Role of Perceived Organizational Support in the Relationship of Procedural Justice with Organizational Commitment - Kaur, Surjit; Bedi, Aneet (Prabandhan: Indian Journal of Management, 2017)
The paper assessed the mediating role of perceived organizational support (POS) between procedural justice and organizational commitment. The study drew its sample from the fast growing and challenging banking industry of India. Procedural justice was found as an important factor for enhancing organizational commitment. POS plays a partial mediating role in this relationship, giving evidence for the existence of other mediating factors, which can be further explored. The findings suggested that the perseverance of procedural justice in an organization is indicative of the support extended to the employees by their organization, and this support stimulates the employees to give enhanced commitment towards their organization. The implications of the study were discussed, and the areas where further research is needed were also highlighted.